An efficient algorithm for low-order direct discrete-time implementation of fractional order transfer functions. (March 2018) - De Keyser, Robin; Muresan, Cristina I.; Ionescu, Clara M.
Abstract: Fractional order systems become increasingly popular due to their versatility in modelling and control applications across various disciplines. However, the bottleneck in deploying these tools in practice is related to their implementation on real-life systems. Numerical approximations are employed but their complexity no longer match the attractive simplicity of the original fractional order systems. This paper proposes a low-order, computationally stable and efficient method for direct approximation of general order (fractional order) systems in the form of discrete-time rational transfer functions, e.g. processes, controllers. A fair comparison to other direct discretization methods is presented, demonstrating its added value with respect to the state of art. Highlights: Direct discrete-time approximation of general functions. Applicable to any non-rational polynomial. Algorithm delivers stable and minimal-order result.